T2 Oestrogen: an endogenous agonist for trpm3 triggered sensory nerve activation in the airway?. (15th November 2017) - Bonvini, SJ; Wortley, MA; Adcock, JJ; Dubuis, E; Bolaji, JA; D'Sa, S; Ma, J; Birrell, MA; Belvisi, MG
Abstract : Introduction: In chronic lung diseases, activation of airway sensory nerves initiates respiratory reflexes including cough for which there is currently no safe and effective treatment. Ion channels on sensory afferents can activate these reflexes and as such are attractive therapeutic targets. Using synthetic ligands we have shown that activation of TRPM3 can trigger human and guinea pig airway sensory nerves. 1 As TRPM3 is thought as a "steroid receptor" and women are consistently over represented in chronic cough clinics, 2 we hypothesised that oestrogen could be an endogenous agonist of TRPM3 mediated activation of airway sensory nerves. Methods: Ex vivo tissue and neuron assay systems were employed, in conjunction with in vivo electrophysiology and a guinea pig cough model to investigate this hypothesis. Results: In vivo, β-oestradiol caused firing of both C and Aδ fibres and also elicited a cough response in conscious unrestrained guinea pigs. Ex vivo, β-Oestradiol caused a concentration dependant depolarisation of isolated guinea pig vagal nerves which was inhibited by the non-selective ER receptor antagonist ICI182780 (92.7%±4.5%) and by the TRPM3 antagonist Isosakuranetin (86.5%±6.8%). The ER receptor antagonist had no effect on the TRPM3 aganist (CIM0216) mediated depolarisation. Translational responses were obtained in human vagal tissue. Single cell PCR indicated that the TRPM3 ion channel and two oestrogen receptors GPER and ERα were expressed in airway specific nodose and jugular ganglia, and were co-expressed with TRPM3. Conclusion: These data show that the oestrogen can activate airway sensory nerves, and suggests that ER receptors may be activated upstream of TRPM3 activation. Further investigation is required, however this data may help to explain the higher number of females attending chronic cough clinics and suggests TRPM3 could be a novel therapeutic target for chronic cough. References: Bonvini et al . AJRCCM 2017;195:A7047. Kelsall et al . Thorax 2009;64:393–8.